PERSEPSI PETANI TERHADAP USAHATANI LAHAN PEKARANGAN (STUDI KASUS USAHATANI LAHAN PEKARANGAN DI KECAMATAN KERINCI KABUPATEN PELALAWAN) - Cepriadi '; Roza Yulida (Fakultas Pertanian, Universitas Riau, 2012)
Farm yard use is an innovation for farmers, while farmers' perceptions of innovationcharacteristics greatly influence the sustainability of the farm yard. The purpose of thisstudy is to determine the perceptions of farmers about farm yard use in the Kerinci District.The study was done by survey, where interviwed to 30 respondents, used simple randomsampling tecnique. The results showed that the perception of the farmers is very good. Thisis indicated by the number of scores obtained in the amount of 1,381. Judging from therelative advantage by farmers, farming is highly beneficial both in terms of consumptionand in terms of the economy. The farmers also found it is quite suitable for farming on theirland. It can be seen from the results of their production is quite good, the perceived level ofcomplexity is lowest. This is because most of the respondents said that it is not only veryeasy to implement farm yard, but also they have farming experience before joining theprogram.Key word: Farm yard, innovation, perception,